A sensitive assay of mercury using fluorescence correlation spectroscopy of gold nanoparticles. (7th November 2014) - Xu, Zhancheng; Lan, Tao; Huang, Xiangyi; Dong, Chaoqing; Ren, Jicun
Abstract We described a new and sensitive method for the determination of mercury ions (Hg2+) on the basis of fluorescence correlation spectroscopy (FCS) and recognition of oligonucleotides. In this assay, 30‐nm gold nanoparticles (GNPs) were modified with oligonucleotides containing thymine bases (T) as fluorescent probes, and the principle of this assay was based on the specific binding of Hg2+ by two DNA thymine bases. When two GNPs labelled with different oligonucleotides were mixed with a sample containing Hg2+, the T‐Hg2+‐T binding reaction should cause GNPs to form dimers (or oligomers), which would lead to a significant increase in the characteristic diffusion time of GNPs in the detection volume. The FCS method is a single molecule detection method and can sensitively detect the change in the characteristic diffusion time of GNPs before and after binding reactions. The quantitative analysis was performed according to the relation between the change in the characteristic diffusion time of GNPs and the concentration of Hg2+. Under optimal conditions, the linear range of this method was from 0.3 nM to 100 nM, and the detection limit was 0.14 nM for Hg2+. This new method was successfully applied for direct determination of Hg2+ levels in water and cosmetics samples. Copyright © 2014 John Wiley & Sons, Ltd.